Efektifitas Kegiatan Gopyokan Tikus Sawah (Rattus argentiventer) di Desa Bener, Kabupaten Klaten - Bonjok Istiaji; Swastiko Priyambodo; Anna Ardillah Sanmas; Ainur Rosidah (Jurnal Pusat Inovasi Masyarakat (PIM), 2020)
Rice field rat assault in Bener Village according to participatory mapping indicates assault the most severe among other villages, in Wonosari Sub-district, Klaten District. rice-field rat has induced a lot of rice fields to fail harvest and left to dry or fallow for the past few years. The program aims to control rice field rats in Bener Village through a gropyokan. The Program began by gather Gapoktan leaders and farmers to explain the activities to be held. In the implementation of gropyokan combined with sulfur fumigation, a sequence of activities can eradicate or repel rats. Furthermore, socialization execute to farmers concerning the breed of rats and demonstration of fumigator. Restraint has been done in Gapoktan rice fields and is prospective as an example for other farmers in controlling rice field rat assaults. Keyword: fumigation, gropyokan, rice-field rat